2015
DOI: 10.1115/1.4031941
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Decompression Wave Speed in Pure Carbon Dioxide and Comparison With Predictions by Equation of State

Abstract: Carbon dioxide capture and storage (CCS) is one of the technologies that have been proposed to reduce emissions of carbon dioxide (CO2) to the atmosphere. CCS will require the transportation of the CO2 from the “capture” locations to the “storage” locations via large-scale pipeline projects. One of the key requirements for the design and operation of pipelines in all jurisdictions is fracture control. Supercritical CO2 is a particularly challenging fluid from this point of view, because its thermodynamic chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…In this study, we also found that very small values of this coefficient (C < 10 s −1 ) caused convergence problems Thus, the range of C was chosen from 10 s −1 to 1000 s −1 . This suggests that the results are in accordance with the results obtained by Brown et al, 40 who pointed out that a smaller pressure drop was observed when the relaxation time was reduced. The positions where the pressures measured are shown in Table 1.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, we also found that very small values of this coefficient (C < 10 s −1 ) caused convergence problems Thus, the range of C was chosen from 10 s −1 to 1000 s −1 . This suggests that the results are in accordance with the results obtained by Brown et al, 40 who pointed out that a smaller pressure drop was observed when the relaxation time was reduced. The positions where the pressures measured are shown in Table 1.…”
Section: Resultssupporting
confidence: 92%
“…The test was conducted at the TransCanada pipeline Gas Dynamic test facility at Didsbury, Alberta, Canada, by Botros et al 40 They also presented a one-dimensional HEM model coupled with GERG-2008 EOS to calculate the decompression wave speed. The test was conducted at the TransCanada pipeline Gas Dynamic test facility at Didsbury, Alberta, Canada, by Botros et al 40 They also presented a one-dimensional HEM model coupled with GERG-2008 EOS to calculate the decompression wave speed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Test designation numbers originally used in Botros et al are retained here to maintain consistency. A brief description of the shock tube test rig and test procedure is provided below, and more details are given in Botros et al The experimentally determined decompression wave speeds ( W ) are compared to predictions using the GERG‐2008 EOS and the Peng‐Robinson (PR) EOS, as implemented in REFPROP…”
Section: Introductionmentioning
confidence: 99%